Case report of ventral hernia complicating bariatric surgery - Sarwal, Ankush (J Minim Access Surg, 2018)
Ventral hernias (VHs) are common in the bariatric population with incidence of around 8% of patients undergoing laparoscopic Roux-en-Y gastric bypass (LRYGB). The factors contributing to the incidence of VH includes high intra-abdominal pressures, previous histories of abdominal surgeries, defects in fascial structure and reduced healing tendency. There is a high index of suspicion in BS patients with VH for hernia complications which can be lethal after LRYGB. Here, we present a case where VH complicated the LRYGB surgery.